A-synuclein prion strains differentially adapt after passage in mice. - Sara A M Holec; Chase R Khedmatgozar; Shelbe J Schure; Tiffany Pham; Amanda L Woerman (PLoS Pathogens)
In patients with synucleinopathies, the protein α-synuclein misfolds into multiple conformations, each of which determines whether a patient develops multiple system atrophy (MSA) or one of three Lewy body diseases (LBDs). However, patients may also first present with pure autonomic failure, which strictly impacts autonomic nerves in the periphery, which can then phenoconvert into MSA or a LBD. When neuroinvasion happens, it remains unknown if strain properties are retained or if strain adaptation occurs, even though neuroinvasion of some prion protein (PrP) strains is known to result in the emergence of novel PrP strain variants. To investigate this question in synucleinopathies, we inoculated TgM83+/- mice, which express human α-synuclein with the A53T mutation, with a mouse-passaged MSA patient sample either intracranially (i.c.) or into the sciatic nerve (sc.n.), and compared the biochemical and biological properties of α-synuclein prions in the brains of terminal mice. Importantly, while i.c. and sc.n. transmission studies generated pathogenic α-synuclein with similar properties, both the primary and secondary passaged MSA samples had different infectivity profiles in a panel of α-syn140-YFP cells than the starting MSA patient sample, indicating that MSA prions adapt during initial passage in TgM83+/- mice. Similarly, using i.c. inoculation of A53T preformed fibrils to study strain selection, we found both biochemical and biological evidence that mouse passage exerts a selective pressure on α-synuclein prions in which a sub-population of starting conformations emerges in terminal animals. Together, these findings demonstrate that similar conformational selective pressures known to impact PrP prion replication also impact replication of α-synuclein prions.